Prediction of Longitudinal Compressive Physical and Mechanical Properties of Bamboo - Yan Yuan; Liming Yang (BioResources)
Some traditional building materials, such as concrete and steel, have a negative impact on the environment. With the in-depth implementation of sustainable development, green materials are gradually being considered, and bamboo is a green high-energy building material. However, there have been few studies on the prediction of mechanical properties of bamboo. In order to predict the longitudinal compressive properties of bamboo, tests were carried out on the longitudinal compressive tests of bamboo. The failure mode was explored, as well as the relationship between the physical and mechanical properties of bamboo. Prediction formulas were developed for the longitudinal compressive properties of bamboo. The results showed that the failure mode of the longitudinal compressive test of bamboo was ductile failure. The wall thickness and diameter of bamboo were found to be positively correlated with height. The longitudinal compressive strength and elastic modulus were positively correlated with height and negatively correlated with wall thickness and diameter. The longitudinal compressive strength and elastic modulus were positively correlated with height. The linear model can be used to fit the relationship between mechanical properties and height. This research provides a reference for the prediction of bamboo properties.